A study on knowledge of the fire evacuation for occupant in commercial high rise building / Mohd Redhuan Jusoh - Jusoh, Mohd Redhuan (Faculty of Architecture, Planning and Surveying, 2010)
Skyscrapers have always been celebrated, admired and enjoyed by many, in the high- rise building can provided with modem technology equipments to assist each occupant to use. Furthermore the safety features is also provided in high rise building but it cannot ensure that the occupants will be safe if the case emergency occur such as fire. When the fire occur in die high- rise building, many people facing the life lost because lack of knowledge about safety and means of escape in the building. Each occupant in the high rise building must have basic knowledge on fire evacuation for self safety. This research is made to identify the effectiveness of fire evacuation provided in the building, to identify on types of safety management to conduct in the high rise building and lastly to identify die knowledge of occupant for the fire evacuation. Methodology for this research is to cany out according to the literature review, data collated from the interviews and questionnaires at case study buildings and the high- rise building users, questionnaires were distributed to occupants in the building, and from the data collected the analysis were carried out to get the result. From the data collected and interviews held with the building safety officers, the research objective is to identify on effectiveness of the fire evacuation in the high rise building and types of die fire safety management to influence in the building which the building management to conduct the types of fire safety in the building such as follow the requirement or not. Lastly the result on the occupants knowledge on die fire evacuation can be found in this research, die lesser in conducting the fire safety management in the building the lesser knowledge of fire evacuation of die occupants.